Pembelajaran Daring: Dampaknya Terhadap Berpikir Kreatif Siswa Dalam Menyelesaikan Masalah - Irdalisa Irdalisa; Fidastiwi Anjani; Mega Elvianasti; Maesaroh Maesaroh (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
This study aims to analyze the creative thinking skills of class XI science students on the material of the respiratory system in solving problems through bold learning. This research was conducted on 32 students of class XI science at a private high school in the city of Jakartain the even semester of the 2020/2021 academic year. The research method used is descriptive research method with a quantitative approach. Research data obtained from the test instrument. Creative thinking skills in this study are thinking skills in developing thinking skills (fluency), flexible thinking (flexibility), original thinking (originality), and elaboration thinking (elaboration). The result of the research on the students' creative thinking ability test as a whole is 42.38% which is included in the very poor category. The ability to think (fluency) of 48.83% is included in the very poor category, flexibility thinking (flexibility) of 34.90% is included in the very poor category, original thinking (originality) is 43.36% is included in the very poor category, and Think elaboration (elaboration) of 50% is included in the category of very less. These results indicate the ability of students to produce various answers to overcome problems in brave learners, including low.